2021
DOI: 10.3389/fped.2021.611007
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Surgical Reconstruction of the Right Ventricle Outflow Tract in Double Outlet Right Ventricle With Mirror Image-Dextrocardia

Abstract: Introduction: The purpose of this study was to report our experience in the surgical reconstruction of the right ventricular outflow tract in double outlet right ventricle with a major coronary artery crossing the right ventricular outflow tract in the presence of mirror image-dextrocardia.Methods: From January 2005 to December 2019, 19 double outlet right ventricle patients (median age 4 years) with mirror image-dextrocardia and a major coronary artery crossing the right ventricular outflow tract received sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…8,9 In the present case, the pathogenesis of cerebrovascular occlusion may not have been related to dextrocardia because dextrocardia does not lead to posterior circulation cerebrovascular stenosis, and dextrocardia itself has no hemodynamic abnormalities. 8,9 Considering the history of hypertension and the angiographic results of emergency thrombectomy, we considered that the pathogenesis of this patient was vascular stenosis and occlusion caused by atherosclerosis. Whether dextrocardia causes cerebrovascular stenosis and occlusion requires the analysis of additional cases.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…8,9 In the present case, the pathogenesis of cerebrovascular occlusion may not have been related to dextrocardia because dextrocardia does not lead to posterior circulation cerebrovascular stenosis, and dextrocardia itself has no hemodynamic abnormalities. 8,9 Considering the history of hypertension and the angiographic results of emergency thrombectomy, we considered that the pathogenesis of this patient was vascular stenosis and occlusion caused by atherosclerosis. Whether dextrocardia causes cerebrovascular stenosis and occlusion requires the analysis of additional cases.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that mirror-image dextrocardia is a real form of dextrocardia. 8 Our patient’s visceral inversion was associated with mirror-image dextrocardia. This type of heart is on the right side of the chest.…”
Section: Discussionmentioning
confidence: 65%
“…A variety of materials can be used for RVOT reconstruction, as described in our previous series study [12][13][14]. However, pediatric patients' options are limited to homograft, bovine jugular vein conduit, and valved conduits sewn by hand using pericardium or expanded polytetrafluoroethylene (ePTFE) due to size limitations.…”
Section: Discussionmentioning
confidence: 99%